A functional CD86 polymorphism associated with asthma and related allergic disorders. Issue 8 (18th May 2007) - Corydon, Thomas Juhl; Haagerup, Annette; Jensen, Thomas Gryesten; Binderup, Helle Glud; Petersen, Mikkel Steen; Kaltoft, Keld; Vestbo, Jørgen; Kruse, Torben Arvid; Børglum, Anders Dupont
Abstract : Background: Several studies have documented a substantial genetic component in the aetiology of allergic diseases and a number of atopy susceptibility loci have been suggested. One of these loci is 3q21, at which linkage to multiple atopy phenotypes has been reported. This region harbours the CD86 gene encoding the costimulatory B7.2 protein. The costimulatory system, consisting of receptor proteins, cytokines and associated factors, activates T cells and regulates the immune response upon allergen challenge. Methods: We sequenced the CD86 gene in patients with atopy from 10 families that showed evidence of linkage to 3q21. Identified polymorphisms were analysed in a subsequent family-based association study of two independent Danish samples, respectively comprising 135 and 100 trios of children with atopy and their parents. Functional analysis of the costimulatory effect on cytokine production was performed in an autologous cell-based system based on cells expressing CD86 variants. Results: Two polymorphisms were identified, encoding the amino acid changes Ile179Val and Ala304Thr, respectively. Significant associations were observed between the Ile179Val polymorphism and allergy phenotypes in both samples (eg, asthma, p = 4×10 −3 in the two samples combined). The undertransmitted (protective) Val179 allele was found to induce higher production of both Th1 and Th2 cytokines than the overtransmitted (risk) Ile179 allele, suggesting a functional impact of the polymorphism. Conclusion: The CD86 gene, and specifically the Ile179Val polymorphism, may be a novel aetiological factor in the development of asthma and related allergic disorders.